Clinical Characteristics of Measles in Infancy: A Hospital Based Study - Rahat, Farhana; Abiduzzaman, MF; Choudhury, Ahmed Murtaza (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: There is a global resurgence of measles among children in recent years and a number of infants are being affected. Objectives: The aim of the study was to determine the frequency of measles in infancy and to describe their clinical characteristics in a tertiary care children hospital. Methods: A prospective observational study was conducted in Dr. MR Khan Shishu Hospital and Institute of Child Health from March, 2019 to February, 2020. The children who came with signs and symptoms of measles, like fever with maculopapular rash associated with cough, runny nose and conjunctivitis were recorded and frequency of measles in infants among hospitalized measles patients was noted. Infants with measles were enrolled for the study and their clinical characteristics, complications and outcome were determined. Data were analyzed by SPSS version 23. Results: A total of 64 infants were studied. The frequency of measles in infants among hospitalized measles patients was 43%. Forty seven percent infants were between 9 to 10 months. Clinical features were typical and all had fever and maculopapular rash. Pneumonia was the main complication and occurred in 50(78%) cases which was followed by oral ulcer 42(66%), diarrhea 26(41%), febrile seizure 9(14%) and croup 5(8%). Thirty four (53%) infant had normal nutritional status. Only 19.51% infant received first dose of measles vaccine. The mortality rate was 2(3%). Conclusion: A number of children are being affected by measles before completing first year of life and they develop complications which are related to morbidity and mortality. So, control and prevention of measles in infancy should give more importance. DS (Child) H J 2020; 36(1) : 20-24